SCADA system simulation for photovoltaic rooftop system (Balkan Journal of Applied Mathematics and Informatics, 2022)
The main goal of this research work is to design and develop an application program for solar PV monitoring in real time. Development of a process for continuous monitoring of energy parameters and updating of data. The implementation of an automatically controlled SCADA system that uses PLC as a controller is important for efficient, reliable and safe operation of the process.                                                  The software programs PVSOL and LabVIEW were used for the needs of the project. LabVIEW fully demonstrates the approach of controlling, processing and displaying output data and visualizing results. The methodology is based on monitoring all field equipment, weather and electrical parameters. The simulation and analysis in LabVIEW help to efficiently utilize solar energy and optimize performance for the theoretical model of a photovoltaic system placed on the roof of a household.
Keywords: solar energy, photovoltaic module, process automation, data acquisition, real-time data monitoring, SCADA, LabVIEW